Characterization of wear of steels before and after nitriding - Hannachi Mohamed Tahar; Bradji Mohammed (University of Eloued, 2019)
Wear is a complex set of phenomena, leading to debris emission with loss of mass, ribs, shape, and accompanied by physical and chemical surface transformations. Thermochemical treatments (nitriding) directly cause increased hardness of steel surfaces and contribute to strength and improvement against the effects of layer wear
Intervention
Keywords: nitriding; wear; loss mass; time; hardness